Integrating Ecocritical Values in Kaba Minangkabau into Literary Criticism Learning - Nofrahadi Nofrahadi; Mohamad Hafrison; Rizaldy Hanifa; Suhailee Sohnui; Riki Muhamanda (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2025)
The global environmental crisis demands educational innovations that can foster ecological awareness among students. Literature, especially kaba Minangkabau, contains values of nature conservation that can be utilized as a learning resource. This study aims to integrate the values of ecocriticism in kaba Minangkabau into literary criticism learning in higher education to produce contextual, locally-based learning that supports the implementation of Merdeka Belajar Kampus Merdeka (MBKM) and perguruan tinggi berdampak. The research approach used was qualitative with a case study design. Data were collected through in-depth interviews, focus group discussions, classroom observations, and documentation studies of 6 lecturers and 18 students from UNP, Unes, and UPGRISBA. Data analysis was conducted using an interactive model. The results showed that lecturers and students were highly interested in using kaba, but were constrained by the limited availability of ecocritical textbooks. Content analysis of the seven kabareveals four main themes of ecocriticism, namely depictions of nature, natural disasters/devastation, the relationship between humans and nature, and the author's attitude. This research produced a textbook model that combines literary criticism theory, ecocritical analysis guidelines, kaba case studies, and reflective activities in accordance with CPMK, thereby strengthening students' ecological literacy and encouraging pro-environmental awareness and action.